Civil liberties & human rights - Helen fenwick , Richard glancey (Routledge revision, 2014)
More than merely describing developments in the field of civil liberties and human rights, this comprehensive and challenging textbook provides students with detailed and thought-provoking coverage and analysis of the impact of the Human Rights Act 1998 in an era in which human rights are coming increasingly under pressure.